2010
DOI: 10.1182/blood-2009-09-244327
|View full text |Cite
|
Sign up to set email alerts
|

The mutation N528S in the von Willebrand factor (VWF) propeptide causes defective multimerization and storage of VWF

Abstract: We characterized a consanguineous Turkish family suffering from von Willebrand disease (VWD) with significant mucocutaneous and joint bleeding. The relative reduction of large plasma von Willebrand factor (VWF) multimers and the absent VWF triplet structure was consistent with type 2A (phenotype IIC) VWD. Surprisingly, platelet VWF was completely deficient of multimers beyond the VWF protomer, suggesting defective ␣-granular storage of larger multimers. Patients were nearly unresponsive to desmopressin acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 40 publications
5
39
0
Order By: Relevance
“…This suggests that the primary processing defect may lie upstream at the point of transcription, as reported previously by Nichols et al, and may be similar to the previously reported type 2A variant N528S-VWF. 29,31 In contrast, several variants were secreted efficiently, but had various degrees of multimer abnormalities, including C1099P, C1190S, C1272S, and C1272Y. These variants were placed in an "unclassified" group because they did not seem to fit into either of the 2 traditional groups for type 2A VWD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the primary processing defect may lie upstream at the point of transcription, as reported previously by Nichols et al, and may be similar to the previously reported type 2A variant N528S-VWF. 29,31 In contrast, several variants were secreted efficiently, but had various degrees of multimer abnormalities, including C1099P, C1190S, C1272S, and C1272Y. These variants were placed in an "unclassified" group because they did not seem to fit into either of the 2 traditional groups for type 2A VWD.…”
Section: Discussionmentioning
confidence: 99%
“…22,24,33 The impact of mutations in VWF on formation of storage granules has been investigated for few variants. 17,26,29,30,[34][35][36] A loss of regulated storage was characteristic of the "classic" group 1 variants, which did not form Weibel-Palade body-like storage granules and had only a diffuse staining pattern in HEK293 cells. The group 2 variants G1579R and I1568N formed storage granules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in these cell lines have provided insights into the effects of VWF mutations on the storage and secretion of VWF. [11][12][13][14][15][16][17] In contrast, the use of nonendothelial cell systems has obvious limitations: The possible gross overexpression of recombinant VWF on transfection may influence interpretation of the data, and the exocytotic machinery is probably different from that of endothelial cells. Mimicking the heterozygous state of VWF mutations by cotransfection of wild-type and mutant VWF is potentially also problematic.…”
Section: Introductionmentioning
confidence: 99%
“…The phenotype of this mutation was defective multimerization, storage and secretion. The introduction of a new glycosylation site could potentially affect the interaction of the propeptide with mature VWF or disrupt the nearby CGLC disulphide isomerase sequence, that is implicated in VWF multimerization 38 As well as the specific effect on disulphide bond formation in the CK domain, all the glycan mutants presented an overall increased free thiol reactivity compared with wtVWF. Removal of N-linked glycan chains may therefore lead to a more open VWF conformation allowing exposure and detection of previously buried cysteine residues.…”
mentioning
confidence: 99%